The Influence of Service Quality, Relationship Quality on Port Performance Which has Implications For Customer Satisfaction at The Port Tg. Priok Jakarta Indonesia - Rachman, Abdul; Wahid, Ahmad (Green Publisher, 2023)
This study aims to examine and analyze the effect The Influence of Service Quality, Relationship Quality On Port Performance Which Has Implications For Customer Satisfaction At The Port Tg. Priok Jakarta Indonesia. The influence of the organization on the performance of Jakarta's Port tg.priok was studied with regard to its organic employees, either partially or indirectly. A sample of 70 people was selected from a population of 100 people using the Slovin formula. This research employs a survey method with descriptive and associative explanation techniques. Data was collected using both descriptive and inferential statistics through Structural Equation Modeling (SEM- SMART PLS). The model consists of sub-structures including Service Quality and Relationship Quality as exogenous variables, Port Performance as an intervening variable, and Customer Satisfaction as the endogenous variable. The primary components of the model consist of two indirect structures: the first examines the effect of Service Quality and Relationship Quality on Port Performance, while the second considers the direct effect of Service Quality and Relationship Quality on Customer Satisfaction. The R Square test on the inner model is one way to measure how much an endogenous variable can be explained by the related exogenous variables. In the following explanation, we will explain in more detail about the R Square concept in the inner model and how its use can help to understand the interrelationships between variables in a model. Following are the results of the regression analysis in this research model: The results showed that there was a positive and significant effect R Square R Square Adjusted Customer Satisfaction 0.493 - 0.471 Port Performance 0.251 - 0.230 . The following are the results of the R Square and R Square Adjusted tests on two endogenous variables in a model, namely Customer Satisfaction and Port Performance. Customer Satisfaction has an R Square of 0.493, which means that around 49.3% of the variation in Cust Satisfaction can be explained by exogenous variables associated with these variables. Meanwhile, the R Square Adjusted is 0.471, which indicates that around 47.1% of the variation in customer satisfaction can be explained by exogenous variables in the model, after taking into account the complexity of the model. Port Performance has an R Square of 0.251, which means that about 25.1% of Port Performance variations can be explained by exogenous variables associated with these variables. Meanwhile, the R Square Adjusted is 0.230, which indicates that around 23.0% of the variation in Port Performance can be explained by exogenous variables in the model, after taking into account the complexity of the model.